2023
DOI: 10.3390/polym15092027
|View full text |Cite
|
Sign up to set email alerts
|

Polyketone-Based Anion-Exchange Membranes for Alkaline Water Electrolysis

Abstract: Anion-exchange membranes (AEMs) are involved in a wide range of applications, including fuel cells and water electrolysis. A straightforward method for the preparation of efficient AEMs consists of polymer functionalization with robust anion-exchange sites. In this work, an aliphatic polyketone was functionalized with 1-(3-aminopropyl)imidazole through the Paal–Knorr reaction, with a carbonyl (CCO %) conversion of 33%. The anion-exchange groups were generated by the imidazole quaternization by using two differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…The polyketone PK-30 has been functionalized using an adaptation of the procedure reported by Racchi et al 9 A schematic representation of the reaction is reported in Figure 1. No solvent is needed since the amine is liquid and the polyketone acts as a viscous liquid at 110 C.…”
Section: Functionalization Of Polyketone and Characterizationmentioning
confidence: 99%
See 4 more Smart Citations
“…The polyketone PK-30 has been functionalized using an adaptation of the procedure reported by Racchi et al 9 A schematic representation of the reaction is reported in Figure 1. No solvent is needed since the amine is liquid and the polyketone acts as a viscous liquid at 110 C.…”
Section: Functionalization Of Polyketone and Characterizationmentioning
confidence: 99%
“…This shift can be related to the presence of sidechains that hinder the backbone mobility as reported in previous investigations. 9 However, the glass transition remains below room temperature. This behavior could result in membranes characterized by good flexibility, which is beneficial for the final application as AEMs.…”
Section: Functionalization Of Polyketone and Characterizationmentioning
confidence: 99%
See 3 more Smart Citations